2021
DOI: 10.1186/s13023-021-01911-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and physical activity patterns in adults and children with Bardet–Biedl syndrome

Abstract: Background Overweight and obesity are common features of the rare disease Bardet–Biedl syndrome (BBS). Sleep and physical activity are behaviors that might impact overweight and obesity and thus may play a key role in the health and well-being of people with BBS. Objectively-measured sleep and physical activity patterns in people with BBS are not well known. We evaluated objectively-measured sleep and physical activity patterns in the largest cohort to date of people with BBS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Forsythe et al did not observe a similar finding (personal communications). Interestingly, similar sex differences were not observed in previous CRIBBS‐based studies examining childhood obesity 31 and sleep and physical activity patterns 67 . Our study has some limitations.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Forsythe et al did not observe a similar finding (personal communications). Interestingly, similar sex differences were not observed in previous CRIBBS‐based studies examining childhood obesity 31 and sleep and physical activity patterns 67 . Our study has some limitations.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, similar sex differences were not observed in previous CRIBBS-based studies examining childhood obesity 31 and sleep and physical activity patterns. 67 Our study has some limitations. Potential risk factors for CKD progression including untreated or suboptimal treatment of hypertension, albuminuria, and metabolic syndrome cannot be comprehensively evaluated based on registry data.…”
Section: Discussionmentioning
confidence: 89%
“…Pomeroy et al observed that strategies to increase sleep duration could be useful to mitigate obesity. 138 In 2009, Seo et al demonstrated that intravenous melanocortin receptor agonist administration reduced body weight and food intake in Bbs knockout mice; 29 interestingly, in November 2020 and July 2021, in USA and EU, respectively, a new drug named setmelanotide has been approved for the treatment of obesity due to mutations in POMC, PCSK1 and LEPR. Setmelanotide is a melanocortin-4 receptor (MC4R) agonist and according to a phase-two study, it mitigates hyperphagia in BBS, reducing weight and hunger.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In a recent study assessing free-living sleep and activity patterns in adults and children with BBS, 77 adults and 71 children (age range 6–18 years) were asked to wear a high-resolution triaxial accelerometer on their wrist for 12 days [21 ▪ ]. Insufficient sleep, defined as a failure to meet sleep recommendations for age, was common with 90% of adults and 92% of children failing to meet sleep recommendations for age.…”
Section: Diabetes Risk Factors In Bardet Biedl Syndromementioning
confidence: 99%